Image and Video Processing and Recognition Based on Artificial Intelligence (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes 23 published papers on Special issues of "Image and Video Processing and Recognition Based on Artificial Intelligence" in the journal Sensors. The purpose of this Special Issue was to invite high-quality and state-of-the-art academic papers on challenging issues in the field of AI-based image and video processing and recognition.